The role of marine sediment diagenesis in the modern oceanic magnesium cycle - Berg, Richard D.; Solomon, Evan A.; Teng, Fang-Zhen (Nature communications, 2019)
The oceanic magnesium cycle is largely controlled by continental weathering and marine authigenic mineral formation, which are intimately linked to long-term climate. Uncertainties in the magnesium cycle propagate into other chemical budgets, and into interpretations of paleo-oceanographic reconstructions of seawater δ 26 Mg and Mg/Ca ratios. Here, we produce a detailed global map of the flux of dissolved magnesium from the ocean into deeper marine sediments (greater than ∼1 meter below seafloor), and quantify the global flux and associated isotopic fractionation. We find that this flux accounts for 15–20% of the output of magnesium from the ocean, with a flux-weighted fractionation factor of ∼0.9994 acting to increase the magnesium isotopic ratio in the ocean. Our analysis provides the best constraints to date on the sources and sinks that define the oceanic magnesium cycle, including new constraints on the output flux of magnesium and isotopic fractionation during low-temperature ridge flank hydrothermal circulation. The oceanic magnesium cycle is closely linked to Earth’s carbon cycle and long-term climate change, due to processes such as continental weathering and authigenic mineral formation. Here, the authors update the global oceanic magnesium budget by quantifying the flux of magnesium from oceans to marine sediments and the associated isotopic fractionation.